Antifreeze Proteins. Report 1. Classification and Mechanism of Action - Gulevsky, A. K.; Relina, L. I. (Problems of Cryobiology and Cryomedicine, 2009)
Modern ideas concerning principles of a modern classification of antifreeze proteins on the basis of concepts of their structures and functioning mechanisms are briefly presented in the review. The hypotheses suggested about functioning mechanisms of antifreeze proteins and glycoproteins of different origin are reviewed.